Refractory Bricks in the Quebracho Extract Industry, Province of Santa Fe, Argentina - Pasquali, Cristina (Centro de Estudios de Arqueología Histórica (CEAH) de la Universidad Nacional de Rosario, 2024)
The establishment of the quebracho extract industry in the northern region of the province of Santa Fe, Argentina, allows us to investigate within the framework of historical archaeology a trajectory of capitalism along with the relationships and transformations of structures, artefacts and a new social order in the region. The new industry led to a considerable demand for refractory bricks, mostly from Great Britain and the United States, for the installation of boilers, ducts and chimneys. The aim of this work is to advance in the study of commercial brands, origins and commercialisation of refractory bricks identified in the towns of Villa Guillermina, La Gallareta, Tartagal, Villa Ana and Santa Felicia and in the rural area of Mocoví. The sample includes bricks identified in situ and in surface collections, as well as those provided by neighbours and cultural managers. For the determination of commercial brands and the study of the commercialisation of the product, primary sources and specialised bibliographic sources were analysed. This contribution is part of the research carried out within the framework of the Las Forestales y sus pueblos Project, which has been housed -since 2013- at the Centro de Estudios de Arqueología Histórica, Facultad de Humanidades y Artes, Universidad Nacional de Rosario.